2023
DOI: 10.24072/pcjournal.307
|View full text |Cite
|
Sign up to set email alerts
|

A global Corynebacterium diphtheriae genomic framework sheds light on current diphtheria reemergence

Mélanie Hennart,
Chiara Crestani,
Sébastien Bridel
et al.

Abstract: Background: Diphtheria, caused by Corynebacterium diphtheriae, reemerges in Europe since 2022. Genomic sequencing can inform on transmission routes and genotypes of concern, but currently, no standard approach exists to detect clinically important genomic features and to interpret emergence in the global C. diphtheriae population framework. Methods: We developed the bioinformatics pipeline diphtOscan (available at https://gitlab.pasteur.fr/BEBP/diphtoscan) to extract from genomes of Corynebacteria of the dipht… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…Our study extends earlier local observations 11,12,27 , and has enabled a thorough analysis of the event at continental scale. The simultaneous expansion of multiple GCs across several reporting countries is consistent with genomic investigations of a previous outbreak 20 .…”
Section: Main Textsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study extends earlier local observations 11,12,27 , and has enabled a thorough analysis of the event at continental scale. The simultaneous expansion of multiple GCs across several reporting countries is consistent with genomic investigations of a previous outbreak 20 .…”
Section: Main Textsupporting
confidence: 86%
“…The Centers for Disease Control (CDC), the WHO, and guidelines of many European countries recommend either erythromycin or penicillin as first line treatment (https://www.cdc.gov/diphtheria/clinicians.html). Previous studies reported resistance to erythromycin 25,26 , including a recent association with penicillin reduced susceptibility in C. diphtheriae isolates from North and Western Africa 27 .…”
Section: Implications Of the 2022 European Outbreakmentioning
confidence: 96%
“…Despite this, the risk of dissemination within high-vaccination countries seems limited. In France in 2023, no secondary cases were reported, as also observed for cases imported from other areas in 2022 [9].…”
Section: Discussionmentioning
confidence: 64%
“…Gene pbp2m typically confers low-level resistance to penicillin and amoxicillin [8]. In our previous global genomic survey, we reported pbp2m in less than 5% of non-duplicate C. diphtheriae isolates [9]. Here, six of 10 isolates were carrying pbp2m, a remarkable observation given that these isolates belong to ten distinct genomedefined types.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation